Species-dependent energy transfer of surfactant-dispersed semiconducting single-walled carbon nanotubes - Chan-Park, Mary B. (2011)
Single-walled carbon nanotubes (SWNTs) are stabilized with sodium dodecyl sulfate (SDS) micelles in aqueous solution. Aggregation among semiconducting SWNTs can be identified by exciton energy transfer (EET) features in photoluminescence excitation (PLE) mapping. Addition of o-dichlorobenzene (ODCB) not only changes the micelle structure but also induces the aggregation among SWNT species, leading to drastic changes in the EET features of the ensemble. Force-field and molecular dynamic simulation confirm that SWNT bundles are energetically favorable at room temperature. Observed EET features in PLE mappings are found to be SWNT species-dependent. Moreover, the rapid bundling process induced by ODCB allows us to obtain SWNT bundles which are potentially useful for optical and optoelectronic applications.